2010
DOI: 10.1038/npp.2010.131
|View full text |Cite
|
Sign up to set email alerts
|

Scopolamine Produces Larger Antidepressant and Antianxiety Effects in Women Than in Men

Abstract: Some antidepressant agents generate differential benefit based on gender. Blocking cholinergic muscarinic receptors using scopolamine produces robust and rapid antidepressant effects in males and females combined. This study evaluated if males and females differ in the antidepressant response magnitude following scopolamine administration. A total of 52 male and female outpatients meeting criteria for recurrent major depressive or bipolar disorder participated in a double-blind, randomized, placebo-controlled,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 50 publications
2
90
1
Order By: Relevance
“…Of note, however, a compound with a melatonin agonist action has shown some promise in clinical studies (Green, 2011;Sansone and Sansone, 2011). Some investigators have reported an AD-like effect of scopolamine in humans (Furey and Drevets, 2006;Drevets and Furey, 2010;Furey et al, 2010), although other articles have reported negative effects (Howland, 2009). In addition, the positive studies used an atypical treatment design, with scopolamine being given intravenously over 3 consecutive days (Furey and Drevets, 2006;Drevets and Furey, 2010;Furey et al, 2010).…”
Section: Antidepressant-like Effectsmentioning
confidence: 99%
“…Of note, however, a compound with a melatonin agonist action has shown some promise in clinical studies (Green, 2011;Sansone and Sansone, 2011). Some investigators have reported an AD-like effect of scopolamine in humans (Furey and Drevets, 2006;Drevets and Furey, 2010;Furey et al, 2010), although other articles have reported negative effects (Howland, 2009). In addition, the positive studies used an atypical treatment design, with scopolamine being given intravenously over 3 consecutive days (Furey and Drevets, 2006;Drevets and Furey, 2010;Furey et al, 2010).…”
Section: Antidepressant-like Effectsmentioning
confidence: 99%
“…While some patients respond to existing medications, currently available antidepressants take weeks to months to have an effect, and many patients are considered treatment resistant because they fail to respond to 2 or more antidepressants (5). Recent studies demonstrate that scopolamine, a nonselective muscarinic acetylcholine (ACh) receptor (mAChR) antagonist, and ketamine, an NMDA receptor antagonist, produce rapid antidepressant actions (within hours) and are effective even in treatment-resistant MDD patients (6)(7)(8). The rapid antidepressant actions of scopolamine and ketamine are dependent on glutamate release and induction of new spine synapses in the medial prefrontal cortex (mPFC) (9)(10)(11), effects that directly target the synaptic pathophysiology of MDD and chronic stress (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…So, for example, the combination of scopolamine (which has recently been shown to have antidepressant activity and presumably works via muscarinic receptor blockade 28 ) with exercise (which may act via serotonergic and opioid pathways) may target 3 different neurotransmitter systems. This would presumably be preferable to combining a selective serotonin reuptake inhibitor (SSRI) with exercise, which also may have an action on serotonin.…”
mentioning
confidence: 99%